Methemoglobinemia and hemolytic anemia after COVID-19 infection without identifiable eliciting drug: A case-report. (2021) - Lopes, Desirée Verde; Lazar Neto, Felippe; Marques, Lais C.; Lima, Rodrigo B.O.; Brandão, Antonio Adolfo Guerra Soares
Abstract: We report a second case of methemoglobinemia and non-autoimmune hemolytic anemia after contracting the SARS-CoV-2 infection in the absence of an identifiable eliciting drug. A 35-year old male without previous known comorbidities was admitted after he was diagnosed with the COVID-19 infection and had large pulmonary involvement. Seven days later, he desaturated but was without any signs of respiratory distress. A check of arterial blood gas revealed normal partial pressure of oxygen and follow-up tests confirmed a methemoglobinemia diagnosis. Over the next few days, hemolysis was established after decreased levels of hemoglobin and increased levels of indirect bilirubin and lactate dehydrogenase. A hemolytic anemia investigation panel came back normal, including G6PD. A second G6PD test was ordered at the 5-month follow-up appointment and revealed decreased levels. Clinicians should thus be aware of possible false negative tests when testing for G6PD during hemolytic crisis. In addition, whether the COVID-19 infection alone would be responsible for this chain of events remains a challenging question.